Pengembangan Pelaksanaan Discharge Planning dengan Penyusunan Panduan Berbasis Knowledge Management SECI Model - Nanang Miftakhul Wakhdi; Hanny Handiyani; Tuti Afriani; Nurdiana Nurdiana (Journal of Telenursing (JOTING), 2021)
This study aims to identify the development of discharge planning implementation, which is attempted by compiling a discharge planning guide based on the knowledge management SECI Model. The method used is a pilot project that starts from the problem, analyzes problems, prioritizes, prepares action plans, implements and evaluates structures and discussions based on literature review. The results showed that nurses' knowledge of care planning needed further improvement, while perceptions of care planning wanted a revision of standard operating procedures. In conclusion, the implementation of discharge planning can be done by optimizing the control function either at the head of the room or at the service level, and the SECI model knowledge management method guide is an effort that can assist the discharge planning implementation process. Keywords: Discharge Planning, Knowledge Management, SECI Model